Webinar KERJAYA DALAM IT - Muhammad 'Arif, Mohamad (Faculty of Computing, 2021)
PEKAN, 26 Jun 2021 - A Webinar towards industry perspective with the title 'Webinar Kerjaya Dalam IT' was organized by XJC Community.